Ethics in procurement: A case study in a logistic company - Nor Rokiah Hanum, Md. Haron; Iman Haddad Qaisara Dhia, Mohd Mahzan (KnE Social Sciences, 2019)
This paper is part of a preliminary study for the awareness of ethical behaviors in procurement process specifically in a logistic company in Malaysia. Ethic is a critical behavior in a business transaction where most of the people misconduct the behavior unintentionally. The objective of this preliminary study is to get an insight view of a logistic case company, where it is found that ethics is being implemented in the daily procurement process. A structured interview question with various research of past problems concerning ethical behavior addresses the responsiveness of employees behaving ethically by following the ethical guidelines set by the company. This paper proposes that the company need to emphasize the importance of implementation of ethics and also create more awareness by having an official ethical guidelines of the company, despite the fact that the company is small and has a small number of employees. The company has gained many benefits such as cost reduction and maintaining a company-supplier relationship through the implementation of ethics in procurement.